2022
DOI: 10.1002/admt.202200284
|View full text |Cite
|
Sign up to set email alerts
|

A Full Textile Capacitive Woven Sensor

Abstract: In this paper, a full textile capacitive woven sensor integrated over a textile substrate is presented. The sensor consists in an interdigitated capacitance prepared to measure moisture and/or presence detection. In order to evaluate the sensor response to moisture, capacitance has been measured by means of an LCR meter from 20 Hz to 20 kHz in a climatic chamber with a swept of the relative humidity (RH) from 30% to 90% at 20 °C. Subsequently, presence response is evaluated measuring the capacitance of the wov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…We envision that such machines could be used to make Litz wire or woven micro-textiles for applications such as soft actuation 35 and smart textile wearables. 36 Other future work might focus on the development of machines that can make topologies like knots, pseudoknots, and weaves that consist of multiple layers.…”
Section: Discussionmentioning
confidence: 99%
“…We envision that such machines could be used to make Litz wire or woven micro-textiles for applications such as soft actuation 35 and smart textile wearables. 36 Other future work might focus on the development of machines that can make topologies like knots, pseudoknots, and weaves that consist of multiple layers.…”
Section: Discussionmentioning
confidence: 99%
“…However, these sensors are not fully integrated in textile seats. In this sense, the authors demonstrated the functionality of a fully integrated woven capacitive sensor for seat occupancy detection [5]. Based on this previous work, in this paper a textile sensor array is integrated on the base and backrest of a car seat to measure the driver's posture, providing useful information to prevent traffic accidents.…”
Section: Introductionmentioning
confidence: 99%
“…The research in [ 9 ] on novel textile solid-state capacitors based on two-dimensional materials focuses on the use of graphene and boron nitride to create conductive and dielectric fabrics, respectively, which are then integrated to form a textile capacitor. The research includes the preparation of graphene- and h-BN-based inks, as well as the application of these inks on polyester fabrics using a dipping and drying process.…”
Section: Introductionmentioning
confidence: 99%